A stochastic power flow-based static security assessment under uncertain scenarios - Zhang, Yuyue; Tian, Xin; Zhang, Lina (Frontiers in Energy Research, 2024)
With the gradual increase in the grid-connected capacity of renewable energy sources, the uncertainty in the operation of power systems has increased, posing challenges to static security assessment considering N-1 contingency scanning. To address this, this paper first establishes a static security calculation model based on stochastic power flow. Then, it proposes stochastic component-level safety indexes and system-level safety indexes. Finally, using the analytic hierarchy process to analyze the obtained weighting coefficients, the paper establishes a system of static security assessment indexes for power systems. To tackle the high time consumption of multi-scenario static security assessment, which brings difficulties in model debugging and application, a data-driven simulation method based on Extreme Gradient Boosting (XGBoost) is proposed. Case studies based on the IEEE 39-bus system demonstrate the effectiveness of the proposed model and the rapidity of the data-driven approach.